A novel strategy to protect Sutton's nevi during forced or voluptuary exposition to sun rays - Lorenzo Martini (Our Dermatology Online, 2017)
Albeit halo nevi are estimated to be present in approximately 1% of the general population, and they are found to be more prevalent in people with vitiligo, malignant melanoma or Ullrich-Turner' s syndrome, it is not necessary evident that their presence in human body is to be associated to vitiligo and/or melanoma, both genetically and pathophisiologically. In this study I want to demonstrate how it can be safe to expose Sutton's nevi (halo nevi) to all the sun rays (even the most dangerous during all the daylight), employing two natural cosmetic items: the former based on natural juleps made of polychrome algae (and it is to be considered the absorber sun filter) and the latter is a physical sun blocking agent, apt to reflect all the UV rays. The former must be spread onto the halo, the latter, after half an hour, onto the nevus itself.